Advantages of natural microcrystalline graphite filler over petroleum coke in isotropic graphite preparation. (August 2015) - Shen, Ke; Huang, Zheng-Hong; Hu, Kaixin; Shen, Wanci; Yu, Suyuan; Yang, Junhe; Yang, Guangzhi; Kang, Feiyu
Abstract: Graphite materials are used in high-temperature gas-cooled reactor (HTR) as moderator and reflector. Nuclear graphite is currently manufactured using coke as the filler; however, improvements in the performance of nuclear graphite are anticipated in order to enhance the safety and lifetime of HTRs. Natural microcrystalline graphite (MG), which is a metamorphic product of coal, is an emerging candidate as filler material. This paper proposes the approach of preparing isotropic graphite using MG fillers. The characterization results of MG ores and purified powder indicate a polycrystalline and near-isotropic structure of MG particles. Thus, near-isotropic graphite with an isotropy ratio of 1.10–1.15 can be easily obtained via cold isostatic pressing. The thermal diffusivity of MG-based green body is much higher than that of coke-based one, therefore facilitates the baking step. The advantages of MG-based graphite also include a high degree of graphitization, and a low coefficient of thermal expansion, both of which are highly beneficial to nuclear applications. As a result, MG exhibits a large potential for the application in isotropic nuclear graphite.